Getting more than you paid for? Consideration in integrating free and low-cost technologies into translators training programs - Bowker, Lynne; Mcbride, Cheryl; Marshman, Elizabeth (redit - Revista Electrónica de Didáctica de la Traducción y la Interpretación, 2016)
Translation technologies are now an integral part of most translator training programs, and recently, a number of free and low-cost translation tools have begun to appear on the market. Because translator training programs typically have limited budgets, such software has great appeal. However, before adopting these tools, trainers must consider a range of questions, including practical issues, such as laboratory management and language considerations, as well as more pedagogically-oriented questions, including academic priorities, market needs, and possibilities for a wider integration of technologies into translation programs. This paper will explore such questions, and will introduce the Collection of Electronic Resources in Translation Technologies (CERTT) Project, discussing ways in which CERTT could potentially help to maximize the benefits of incorporating free and low-cost software into translator training.